EVALUATION OF GRAIN PROPERTIES OF BUCKWHEAT DEPENDING ON VARIETY - Шакалій, Світлана; Баган, Алла (Modern engineering and innovative technologies, 2024)
This article presents information on the influence of buckwheat varieties on the formation of grain properties. Research was conducted on six varieties (Dykul, Devyatka, Sofia, Volya, Nadiya and Slobozhanka), with such indicators as filminess, yield of c